2017
DOI: 10.1021/acs.jmedchem.7b00241
|View full text |Cite
|
Sign up to set email alerts
|

N6-Substituted 5′-N-Methylcarbamoyl-4′-selenoadenosines as Potent and Selective A3 Adenosine Receptor Agonists with Unusual Sugar Puckering and Nucleobase Orientation

Abstract: Potent and selective A3 adenosine receptor (AR) agonists were identified by replacement of 4′-oxo- or 4′-thionucleosides with bioisosteric selenium. Unlike previous agonists, 4′-seleno analogues preferred a glycosidic syn conformation and a South sugar puckering, as shown in the X-ray crystal structure of 5′-N-methylcarbamoyl derivative 3p. Among compounds tested, N6-3-iodobenzyl analogue 3d was found to be the most potent A3AR full agonist (Ki = 0.57 nM), which was ≥ 800- and 1900-fold selective for A1 and A2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…For the synthesis of final compounds 9a–l , key intermediates, 4′-seleno purine nucleosides 15a–b were synthesized from D-ribose following the previously reported procedures [ 18 , 19 ] ( Scheme 1 ). Briefly, D-ribose was converted to L-lyxonolactone derivative 10 in three steps (oxidation to lactone, conversion of D-ribo configuration to L-lyxo configuration, and tert -butyldiphenylsililyl (TBDPS) protection).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the synthesis of final compounds 9a–l , key intermediates, 4′-seleno purine nucleosides 15a–b were synthesized from D-ribose following the previously reported procedures [ 18 , 19 ] ( Scheme 1 ). Briefly, D-ribose was converted to L-lyxonolactone derivative 10 in three steps (oxidation to lactone, conversion of D-ribo configuration to L-lyxo configuration, and tert -butyldiphenylsililyl (TBDPS) protection).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of a bioisosteric rationale, we recently reported that 4′-seleno analogues of 1 and 2 , i.e., 7 and 8 , were discovered as potent and selective hA 3 AR agonists [ 19 ] ( Figure 2 ). They exhibited comparable A 3 AR binding affinity as the corresponding 4′-oxo- and 5′-thio nucleosides 1 and 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal and C-terminal were truncated (residues 1‒8 and 305‒318). The hA 3 AR homology model was then constructed using Prime [36], based on the crystal structure of the active-state hA 2A AR bound to the selective agonist UK-432,097 as a template (PDB ID: 3QAK) [37]. The disulphide bridge between Cys83 3.25 and Cys166 45.50 in hA 3 AR was conserved.…”
Section: Methodsmentioning
confidence: 99%
“…The replacement of the ribose ring O of Cl‐IB‐MECA with S and Se, that is, 19 a and 19 b , is tolerated with only minor changes in A 3 AR affinity [75] . This was surprising because the Se analogue of Cl‐IB‐MECA 3 has a south conformation in its pure crystalline state, but in the AR binding site a north conformation is required, according to multiple A 1 AR and A 2A AR structures.…”
Section: Design Of Ar Agonists and Their Receptor Interactionsmentioning
confidence: 99%